2023
DOI: 10.3390/su15086781
|View full text |Cite
|
Sign up to set email alerts
|

Green Finance Policy and ESG Performance: Evidence from Chinese Manufacturing Firms

Abstract: While the literature has examined the key role of green finance policy on firms’ green innovation and environmental performance, little attention has been paid to firms’ environmental, social, and governance (ESG) performance, which is increasingly important to stakeholders. Exploiting heterogeneity in firms’ exposure to the green finance pilot zones policy in China in 2017 as a quasi-natural experiment, this paper employs the difference-in-differences model to explore the effect of green finance policy on fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 98 publications
0
24
0
Order By: Relevance
“…For instance, Guangzhou strives to explore the innovation of financial products for new energy automobiles [67]. Huzhou and Quzhou focus on promoting the transformation of traditional high-polluting industries [68].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Guangzhou strives to explore the innovation of financial products for new energy automobiles [67]. Huzhou and Quzhou focus on promoting the transformation of traditional high-polluting industries [68].…”
Section: Discussionmentioning
confidence: 99%
“…Under the concept of green development, heavily polluting enterprises will undoubtedly face more environmental regulations. Due to the regulatory pressure from the government and media, heavily polluting enterprises will be more proactive in strengthening technological innovation to improve environmental management [53]. Additionally, manufacturing polluters are highly sensitive to environmental concerns, so it is simple to elicit a strong response from the market once they communicate green development to the market [54].…”
Section: Analysis Of the Effect Of Contamination Heterogeneitymentioning
confidence: 99%
“…Regarding ESG performance, scholars have focused on its economic consequences and influencing factors. Concerning the influencing factors of ESG performance, Sun et al found that the green finance pilot zone policy had a significant and positive impact on firms' ESG performance [36]. Wang D et al argued that the development of financial technology could alleviate corporate financing constraints by reducing transaction costs and information access costs in the financing process, thereby enhancing firms' ESG performance [37].…”
Section: Esg Performancementioning
confidence: 99%
“…Referring to existing studies [36,37,41], this study selects firm size (Size), gearing ratio (Lev), CEO duality (Dual), profitability (Roa), firm growth (Growth), operating cash flow (Cashflow), board size (Board), board independence (Indep), equity concentration (Top1), and the nature of ownership (Soe) as control variables. In addition, this study also controls for the year-fixed effect (Year) and industry-fixed effect (Ind).…”
Section: Other Variablesmentioning
confidence: 99%